Chitty Chitty Bang Bang - Broccoli, Albert R., 1909-1996.; Dahl, Roald; Hughes, Ken, 1922-2001.; Van Dyke, Dick.; Howes, Sally Ann.; Jeffries, Lionel; Frobe, Gert, 1913-1988.; Quayle, Anna.; Hill, Benny, 1925-1992.; Robertson Justice, James, 1907-1975.; Helpmann, Robert, Sir, 1909-1986.; Sherman, Richard M., 1928-; et al. (Santa Monica, CA MGM Home Entertainment, 1998)
Eccentric inventor Caractacus Potts creates an extraordinary car called Chitty chitty bang bang. It not only drives--but also flies and floats--as it leads him, his two children and his beautiful lady friend, Truly Scrumptious into a magical world of pirates, castles and adventure. There, the group encounter a host of unforgettable characters, including Baron Bomburst of Vulgaria, his persnickety wife, a lovable village toymaker and an evil child catcher.
Audio CD: California dreamin' / The Mamas & the Papas -- It's my party / Lesley Gore -- Na na hey hey kiss him goodbye / Steam -- Wild thing / The Troggs -- Baby love / Diana Ross & the Supremes -- I can't help myself (sugar pie honey bunch) / Four Tops -- My girl / The Temptations -- Wooly bully / Sam The Sham & the Pharaohs.
Based on the book by Ian Fleming.
Originally released as a motion picture in 1968.
Special features: Optional sing-along feature; original theatrical trailer.
Music and lyrics, Richard M. Sherman, Robert B. Sherman.
Dick Van Dyke, Sally Ann Howes, Lionel Jeffries, Gert Frobe, Anna Quayle, Benny Hill, James Robertson Justice, Robert Helpmann.
Rated G.
Keywords: Automobiles -- Drama; Eccentrics and eccentricities -- Drama; DVD-Video discs; Video (DVD); Video recordings for the hearing impaired; Musical films; Juvenile works; Feature films; Children's films; Drama